The ghost of Juniper Creek - Gilmore, Grace (Gilmore, Grace. Tales from Maple Ridge, 2015)
Logan and his friend, Anthony, spy something white high in the trees near the water, and after a neighbor confirms what Logan's older brother, Drew, told them about the Ghost of Juniper Creek, they summon all of their courage to set a trap